Pedagogy vs. Market Needs: An Appraisal of a Graduate Program in Translation and Interpreting (Journal of Advanced Research in Social Sciences, 2019)
The paper is an evaluation of the professional MA program in Translation and Interpreting in a higher education institution in Tunisia. Two research questions were explored in order to investigate whether the program prepares students for the market needs and to present a complete picture revealing insights from multiple sources. Data were collected in two phases through the use of six instruments including a questionnaire for MA students, a questionnaire for former students, a questionnaire for teachers, a structured interview with the MA coordinator, structured interviews with employers and a qualitative content analysis of the course distributions of the MA program. Data analysis revealed that the program responds to the market needs in translation but not in interpreting. All stakeholders strongly agreed on the need for more practice in interpreting. Based on these findings, some recommendations were put forward. These include mainly the need to reconsider the pedagogy by increasing the amount of learning time, involving additional subjects such as soft, life and marketing skills, and providing professional practices, namely internship opportunities.